FORMULATION AND EVALUATION OF SUSTAINED RELEASE TABLETS OF METOPROLOL SUCCINATE - S, Ashutoshkumar (International Journal of Pharmaceutical & Biological Archive, 2011)
Metoprolol succinate is available in conventional dosage forms, administered four times a day, leading to saw tooth kinetics and resulting in ineffective therapy. The combination of these two drugs in a single dosage form will enhance the patient compliance and prolong bronchodilation. Various polymers, such as hydroxy propyl methylcellulose K4M (HPMC- K4M), hydroxy propyl methylcellulose K100M (HPMC- K100M), xanthan gum, ethyl cellulose and hydroxy propyl methylcellulose phthalate (HPMC-P) were studied. HPMC-P and HPMC- K4M were found to be best in controlling the release. In-vitro dissolution studies were carried out for all the bi-layered tablets developed using USP dissolution apparatus type 2 (paddle). It was found that the tablet FB15-FW3 showed 50% release of salbutamol in first hour and the remaining was released for eight hours. However, metoprolol succinate was found to be released as per the USP specifications. This further confirms the integrity of pure drugs and no incompatibility of them with excipients. Also, formulation of FB15-FW3 has shown required release pattern and complies with all the evaluated parameters and comparable to the marketed formulation.